Deciphering the glycosylome of dystroglycanopathies using haploid screens for lassa virus entry - Jae, Lucas T; Raaben, Matthijs; Riemersma, Moniek; van Beusekom, Ellen; Blomen, Vincent A; Velds, Arno; Kerkhoven, Ron M; Carette, Jan E; Topaloglu, Haluk; Meinecke, Peter; Wessels, Marja W; Lefeber, Dirk J; et al. (Science (American Association for the Advancement of Science), 2013)
Glycosylated α-dystroglycan (α-DG) serves as cellular entry receptor for multiple pathogens, and defects in its glycosylation cause hereditary Walker-Warburg syndrome (WWS). At least eight proteins are critical to glycosylate α-DG, but many genes mutated in WWS remain unknown. To identify modifiers of α-DG, we performed a haploid screen for Lassa virus entry, a hemorrhagic fever virus causing thousands of deaths annually that hijacks glycosylated α-DG to enter cells. In complementary screens, we profiled cells for absence of α-DG carbohydrate chains or biochemically related glycans. This revealed virus host factors and a suite of glycosylation units, including all known Walker-Warburg genes and five additional factors critical for the modification of α-DG. Our findings accentuate the complexity of this posttranslational feature and point out genes defective in dystroglycanopathies.